Time and media markets - Albarran, Alan B.; Arrese, Angel (LEA's communication series., 2003)
This edited collection examines time and its relationship to and impact upon media industries, studying how the media industry views time and makes business and economic decisions based on considerations of time. Contributions from an international set of authors analyze time constraints and competition between different media; the quantity and quality of time spent in media consumption, audience and readership time valuation/costing/pricing; and the emergence of new media businesses around individual time management. Specific topics examined in the volume include: * a philos.